DEVELOPMENT OF JAPANESE QUAIL (Coturnix coturnix japonica) EMBRYO - Tyas Rini Saraswati; Silvana Tana (International Journal of Science and Engineering, 2015)
This experiment was conducted to determine the development of Japanese quail embryo (Coturnix coturnix japonica), through observation and measurement of embryo organ development from the age of one day until hatching. The study used 15 female quails and 5 male quails. 15 female quails were divided into 5 cages, each cage containing 3 quails females and 1 male quail. Eggs which are inserted into an egg incubator is produced when the quail began the age of 3 months. Descriptive observation has been made ​​towards the development of organs in the embryo. Based on the results of the study, the growth and development of quail embryo organs occur in stages until hatching occurred during the 16 days.